The Influence Of Exclusive Breastfeeding On Babies With Mother's Knowledge - Siska Desta Roza (Jurnal Kesehatan Akimal, 2022)
Giving of exclusive breastfeeding to infants is a program which is created by the government to prevent and reduce infant mortality. The benefits of breastfeeding protect children from various inflammatory diseases, such as diarrhea, otitis media, and chronic inflammation of the lower respiratory tract. Breast milk colostrum has 10 to 17 times more immune substances than raw milk (Andayani, D, et al, 2017). UNICEF states that exclusive breastfeeding for infants aged 0 to 6 months can prevent the death of at least 1.3 million children under the age of 5 years. The purpose of this study was to determine whether there was knowledge of mothers with exclusive breastfeeding in Lhokseumawe City. The research design is an analytical survey with a cross sectional approach. The population and sample of this study were all mothers who had babies aged 6 to 11 months that visited the Muara Dua Health Center in Lhokseumawe City. The inclusion criteria with a sample size of 62 people. The research used consecutive sampling technique with computer application software. There are two data analysis used in this study, namely univariate analysis and bivariate analysis. The results of study was concluded that there was an influence between mother's knowledge and giving exclusive breastfeeding by showed p-value 0.006 (p<0.05), with mothers who have good knowledge, which are 8,325 times giving exclusive breastfeeding to their babies more than the mothers who have lack of knowledge with a confidence value of 1.638 - 42.315.